Respuesta :

9514 1404 393

Answer:

   see attached

Step-by-step explanation:

The transformation ...

  j(x) = f(x -a) +b

translates the function f(x) right by 'a' and up by 'b'. Here, your functions are ...

a) g(x) = f(x) +2; translated up 2 units

b) h(x) = f(x -3); translated right 3 units

c) k(x) = f(x +1) -4; translated left 1 unit and down 4 units

__

In the attached graph, the functions are color-coded to match the color identifier in the left column. The original f(x) is orange.

Ver imagen sqdancefan
ACCESS MORE